Manajemen Sistem Kredit Semester untuk Mengoptimalkan Perkembangan Potensi Peserta Didik di Sekolah Menengah Atas - Kinanthi Puspa Riani; Achmad Supriyanto; Wildan Zulkarnain; Kinanthi Puspa Riani; Achmad Supriyanto (Universitas Negeri Malang, 2022)
Abstract: The purpose of this study is to provide information management of semester credit system at senior high school. This research used the qualitative approach with case studies. Data collection techniques in the form of interviews, observation and documentation. The process of data analysis are data condensation, data display, and conclusion drawing/verifications. The results of this study: (1) SKS refers to the constitution of Sisdiknas law number 20 of 2003 and Permendikbud law number 158 of 2014, (2) Deputy head of curriculum do the mapping on selection of students through academic and psychological test, (3) formed the team of SKS, (4) learning in the form of groups and minimize methods lectures, (5) intercultural learning through evaluation review teacher, supervision by means of face to face, and the implementation of the exam for students, (6) found a distribution in UKBM too late and (7) be solved by training or workshop, (8) the output of the program among other students are able to graduate within two years and be able to compete to get into college. Abstrak: Tujuan penelitian ini adalah memberikan informasi manajemen SKS di SMA. Penelitian ini menggunakan pendekatan kualitatif dengan studi kasus. Teknik pengumpulan data berupa wawancara, observasi dan dokumentasi. Proses analisis data dengan data condensation, data display, dan conclusion drawing/verifications. Hasil penelitian ini: (1) SKS mengacu pada UU SISDIKNAS Nomor 20 Tahun 2003 dan Permendikbud Nomor 158 Tahun 2014, (2) Waka Kurikulum melakukan pemetaan pada seleksi peserta didik melalui tes akademik dan psikologi, (3) terbentuk tim penanggungjawab SKS, (4) pembelajaran dalam bentuk kelompok dan meminimalisir metode ceramah, (5) evaluasi melalui review pembelajaran antar guru, supervisi dengan cara face to face, dan pelaksanaan ujian untuk peserta didik, (6) ditemukan hambatan pendistribusian UKBM yang terlambat dan (7) diselesaikan dengan training atau workshop, (8) output program antara lain peserta didik mampu lulus dalam jangka waktu dua tahun dan mampu bersaing untuk masuk ke perguruan tinggi.